FOREIGN EXPERIENCE IN PROMOTING THE IMPLEMENTATION OF INNOVATIVE-INFORMATION TECHNOLOGIES BY FINANCIAL INSTITUTIONS - Popelo, O.V.; Kholiavko, N.I. (The actual problems of regional economy development, 2023)
The article is devoted to the analysis of the foreign experience of stimulating the innovative-information technologies introduction by financial institutions to improve the quality of providing financial services to economic agents in modern conditions. It is proven that the changes created by the introduction of innovative-information technologies are aimed at changing the strategic focus of financial institutions, which leads to changes at the organizational level and at the level of the financial system as a whole. Based on the experience of the leading countries of the world, the advantages for financial institutions that they receive due to the use of innovative-information technologies are outlined, including: improving the quality of providing financial services to consumers by facilitating the process of obtaining them, increasing the value proposition, as well as speeding up the process of obtaining these services; the possibility of using several channels for interaction with consumers of financial services, as well as the remote nature of the relationship; ensuring the stability of financial institutions in conditions of turbulence and uncertainty of the external environment; increasing satisfaction and gaining experience of economic agents from the consumption of financial services; the use of a personalized approach to consumers of financial services; reducing the cost of financial services and increasing profitability due to the reduction of operating costs; use of information for analytics; increasing the transparency and reliability of the movement of financial resources and reducing the overall level of risk. The main principles of the implementation of innovative-information technologies are presented. The possibilities and risks of using digital technologies by financial institutions were analyzed, as well as innovative-information technologies that increase the quality of providing financial services were considered. The foreign experience of state initiatives to stimulate financial institutions to implement digital technologies is outlined. Directions for state stimulation of the introduction of innovative-information technologies by financial institutions are given. Practical recommendations on improving the quality of services provided by financial institutions to economic agents in the new conditions of their work are provided.